3D Printed Cell Culture Chamber for Testing the Effect of Pump-Based Chronic Drug Delivery on Inner Ear Tissue - Jana Schwieger; Anna Sophie Frisch; Thomas S. Rau; Thomas Lenarz; Silke Hügl; Verena Scheper (Biomolecules, 2022)
Cochlear hair cell damage and spiral ganglion neuron (SGN) degeneration are the main causes of sensory neural hearing loss. Cochlear implants (CIs) can replace the function of the hair cells and stimulate the SGNs electrically. The condition of the SGNs and their spatial distance to the CI are key factors for CI-functionality. For a better performance, a high number of neurons and a closer contact to the electrode are intended. Neurotrophic factors are able to enhance SGN survival and neurite outgrowth, and thereby might optimize the electrode-nerve interaction. This would require chronic factor treatment, which is not yet established for the inner ear. Investigations on chronic drug delivery to SGNs could benefit from an appropriate in vitro model. Thus, an inner ear inspired Neurite Outgrowth Chamber (NOC), which allows the incorporation of a mini-osmotic pump for long-term drug delivery, was designed and three-dimensionally printed. The NOC’s function was validated using spiral ganglion explants treated with ciliary neurotrophic factor, neurotrophin-3, or control fluid released via pumps over two weeks. The NOC proved to be suitable for explant cultivation and observation of pump-based drug delivery over the examined period, with neurotrophin-3 significantly increasing neurite outgrowth compared to the other groups.